Amazonian peasant livelihood differentiation as mutuality-market dialectics. Issue 7 (10th November 2018) - Fraser, James Angus; Cardoso, Thiago; Steward, Angela; Parry, Luke
ABSTRACT: Economistic approaches to the study of peasant livelihoods have considerable academic and policy influence, yet, we argue, perpetuate a partial misunderstanding – often reducing peasant livelihood to the management of capital assets by rational actors. In this paper, we propose to revitalize the original heterodox spirit of the sustainable livelihoods framework by drawing on Stephen Gudeman's work on the dialectic between use values and mutuality on the one hand, and exchange values and the market on the other. We use this approach to examine how historically divergent mutuality-market dialectics in different Amazonian regions have shaped greater prominence of either extractivism or agriculture in current livelihoods. We conclude that an approach centered on the mutuality-market dialectic is of considerable utility in revealing the role of economic histories in shaping differential peasant livelihoods in tropical forests. More generally, it has considerable potential to contribute to a much-needed re-pluralization of approaches to livelihood in academia and policy.